Comparative analysis of translatomics and transcriptomics in the longissimus dorsi muscle of Luchuan and Duroc pigs. - Songtao Su; Hailong Hu; Kang Liu; Siqi Liu; Zupeng Luo; Jingsu Yu; Tianyu Jiang; Xiangling Li; Chang Sun; Lin Yu; Yuehui Liang; Lei Zhou (PLoS ONE)
IMF (Intramuscular fat) content is a crucial indicator of meat quality in the livestock industry. However, the molecular mechanisms underlying IMF deposition remain unclear in pigs. In this study, we conducted RNC-seq (ribosome nascent-chain complex-bound RNA sequencing) and RNA-seq (RNA sequencing) analyses on the longissimus dorsi muscle of Duroc pigs (a lean breed) and Luchuan pigs (a fat breed) to uncover the genetic basis for the divergent IMF content. The results show that the overall translation level of Luchuan pigs is significantly higher than Duroc pigs, while there is no significant difference in the transcription level. Enzymes related to fatty acid synthesis and elongation, such as ACACA, FASN, and ELOVL5, are significantly up-regulated at the translation level, while enzymes associated with fatty acid degradation, namely ALDH1B1 and ALDH2, are significantly down-regulated. However, there is no significant difference in their transcription levels. qRT-PCR and Western Blotting experiments for ELOVL5 confirm the reliability of the sequencing results. Additionally, the translation initiation factor eIF4A1, known to positively regulate gene translation, displayed higher expression in Luchuan pigs rather than in Duroc pigs and the 5'UTR structural features of genes involved in translation up-regulation matched the mRNA selectivity of eIF4A1. In conclusion, these findings suggest the up-regulation of the eIF4A1 gene expression in Luchuan pigs may elevate the translation levels of genes related to lipid synthesis through translational regulation, further resulting in an increase in IMF content.